Pengaruh Rapat Arus Dan Temperatur Elektrolit Terhadap Ketebalan Lapisan Dan Efisiensi Katoda Pada Elektroplating Tembaga Untuk Baja Karbon Sedang - Harnowo Supriadi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2013)
ABSTRACT Acid copper electroplating has a quite wide current density and electrolyte temperature range, allowing the diversity of the coating result. The specimen is medium carbon steel AISI 1045, pure copper has a role as anode, and sulfuric acid plays the role of electrolyte.Electroplating process conducted by the variations of current density 2, 3, 4, and 5 A/dm2, and electrolyte temperature 30, 40, and 50oC, which lasted for 10 minutes. The layer resulted was measured its mass and thickness, and then we can obtain its cathode efficiency.From the research, the actual coating thickness deviation obtained against its theoretical value is 0.42 to 18.37%. While the cathode efficiency resulted is between 78.33 to 97.78%. Based on coating thickness and cathode efficiency, the optimum conditions for electroplating process is gained at current density 3 A/dm2 and electrolyte temperature 40oC. Keywords: electroplating, copper, current density, electrolyte temperature, coating thickness, cathode efficiency